Atrial fibrillation is associated with increased risk of erectile dysfunction: A nationwide population-based cohort study. (1st July 2015) - Lin, Wen-Yu; Lin, Chin-Sheng; Lin, Cheng-Li; Cheng, Shu-Meng; Lin, Wei-Shiang; Kao, Chia-Hung
Abstract: Background: Our study aimed to investigate the association between atrial fibrillation (AF) and erectile dysfunction (ED). Methods: A total of 3853 male patients with AF were identified as the AF cohort, and 15, 405 male patients without AF were selected randomly as the control group and matched by age and index years of AF diagnosis. The endpoint of interest in this study was the occurrence of ED. Individuals with prior history of ED, female patients, those with missing information, and those aged 20 years and younger were excluded. Results: The mean follow-up duration was 4.67 ± 3.20 years for the AF patients and 5.04 ± 3.30 years for the non-AF patients. During the follow-up period, the incidence of ED in the AF cohort was 1.65-fold higher than the non-AF cohort (20.6 vs 12.5 per 10, 000 person-years, P  < .001). Stratified by age, the incidence of ED was consistently higher in the AF cohort. After adjustment for patient characteristics, multivariate Cox regression analysis demonstrated that AF and hyperlipidemia remained independent risk factors for ED (hazard ratio [HR] = 1.53, 95% confidence interval [CI] = 1.05–2.24 and HR = 1.96, 95% CI = 1.36–2.81, respectively). Relative to the non-AF cohort without hyperlipidemia, the AF patients with hyperlipidemia were at a higher risk of ED (HR = 2.76, 95% CI = 1.52–5.00). Conclusion: In a large-scale cohort, the incidence of ED was significantly higher in male patients with AF than those without AF.